The impact of price and consumption awareness on residential water demand - Monteiro, H.; Rita Martins; Ramalho, J.J.S.; Esmeralda Ramalho (22nd Annual Conference of the European Association of Environmental and Resource Economists, 2016)
The vast literature estimating residential water demand assumes households are aware of and respond to changes in the tariffs or at least in the average price paid. We show that although water consumption does respond to prices, water conservation can also be promoted by making the consumer more aware of the price paid and the level of consumption. We estimate a discrete continuous choice model of residential water demand with Portuguese household level survey data combined with information from water utilities and from the Portuguese meteorological agency. We find price and income elasticities to be ?0.20 and +0.07, respectively. Nevertheless, the rigidity of demand doesn’t establish the limit of the role that tariffs can have in promoting water conservation. We find that households who are aware of the actual unit price and their consumption level, look at their (electronic) water bill frequently and in detail and pay by direct debit consume on average 53% less. We also provide novel findings on the impact of environmentally-friendly behaviors, rainwater harvesting and availability of alternative water sources. The impacts of weather variables and dwelling and household features are also calculated. We find economies of scale in water consumption related to household size.